Effects of acute aerobic and anaerobic exercise on humoral immune factors in elite athletes - (:unkn) unknown (My University, 2005)
The aim of this study was to investigate the effects of acute aerobic and anaerobic exercise on humoral immune system parameters (IgA, IgG, IgM, C3, C4) in elite sportsman. Forty elite volleyball players and twenty healthy age-matched sedentary subjects were enrolled in this study. Subjects in the exercise group were randomly divided into two groups. Twenty athletes forming Group 1 (G1) performed 30-minutes of aerobic exercise on treadmill after determination of workload using the Karvonen protocol. Twenty athletes forming Group 2 (G2) performed anaerobic exercise for 30 seconds according to the Wingate test protocol. The sedentary subjects were enrolled as the control group. Blood samples were obtained from the control group once and five times from the exercise groups (prior to exercise, immediately post exercise, 4 hours post exercise, and two and five days after the exercise protocol). Immunoglobulin A (IgA) Immunoglobulin G (IgG), Immunoglobulin M (IgM), complement C3 and C4 levels were determined from each sample. Statistical analysis was performed using SPSS for Windows; and comparisons were made using Kruskal Wallis Variance Analysis and Wilcoxon Signed Rank Tests. P<0.05 was considered to be statistically significant. Initial heart rate and blood pressure values were significantly higher in the sedentary group where as IgA and IgG levels of the athletes were higher than the sedentary subjects (p<0.05). C3 and C4 values of the athletes were found to be suppressed immediately after both of the exercise protocols as compared to the pre-exercise values (p<0.05). Four hours post either exercise protocols, none of the values were significant as compared to the pre exercise values. After two and five days of aerobic exercise the IgA, IgG and IgM levels of athletes were significantly increased as compared to pre-exercise levels (p<0.05). In G2 there were no significant changes in IgA, IgG or IgM values. In conclusion, this study suggests that regularly performed moderate exercise affects hormone release and enhances some of the humoral immune system parameters (IgA, IgG or IgM) while maximal exercise stressing the organism suppresses these parameters. But, there still remains a need for further studies to fully explain the mechanism responsible for the influence of exercise on the immune system. © 2005 Taylor and Francis Group, LLC.